Radiation induced defects in M₁₋ₓPrₓF₂₊ₓ (M²⁺ = Ca, Sr, Ba, x = 0.35) solid solutions - Boiaryntseva, I.A.; Shiran, N.V.; Gektin, A.V. (Functional Materials, 2012)
Radiation-induced processes in M₁₋ₓPrₓF₂₊ₓ (M²⁺ = Ca, Sr, Ba, x = 0.35) solid solutions have been studied. It is shown that the radiation coloration of M₀.₆₅Pr₀.₃₅F₂₃₅ crystals is due to the trapping of charge carriers at anion sublattice defects. The efficiency of color centers formation in the investigated solid solutions grows in the row Ca —> Sr —> Ba. It may be caused by the increase of the pre-irradiation defects as a result of the different cluster types formation in M₀.₆₅Pr₀.₃₅F₂₃₅ mixed systems.